1998
DOI: 10.1021/jp972264m
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Effect: A Tool for Identification of Spin State in a Photoinduced Electron-Transfer Reaction

Abstract: The present work addresses the investigation of the influence of substitution on the initial spin state in photoinduced electron-transfer (PET) reactions with a series of four exciplex systems i.e., N-ethylcarbazole (ECZ)−1,4-dicyanobenzene (DCB), 1,4,5,8,9-pentamethylcarbazole (PMC)−DCB, ECZ−1,2,4,5-tetracyanobenzene (TCNB), and PMC−TCNB by means of a low magnetic field (MF) (0.05 T). The two primary intermediates that play major roles in determining the efficiencies of bimolecular PET reactions are the conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
29
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 67 publications
3
29
0
Order By: Relevance
“…29,30,54,55,58,6365 In contrast to that, many studies focusing predominantly on photochemical aspects can be found, suggesting that the exciplex is the initial quenching product even at fairly high permittivities. 28,57,66,67 …”
Section: Introductionmentioning
confidence: 99%
“…29,30,54,55,58,6365 In contrast to that, many studies focusing predominantly on photochemical aspects can be found, suggesting that the exciplex is the initial quenching product even at fairly high permittivities. 28,57,66,67 …”
Section: Introductionmentioning
confidence: 99%
“…It is well established that the photochemical reactions which involve formation of geminate radical-ion-pairs (RIPs, A ÅÀ /D Å+ ) and radical-pairs (RPs) containing a pair of spin-correlated free electrons formed as primary transient intermediates through electron transfer between D and A and bond cleavage/hydrogen abstraction, respectively are susceptible to a magnetic field, either internal or external [3][4][5][6][7]. The initial spin-correlation between the electrons of geminate RIPs/RPs will be either singlet (S) or triplet (T) depending on the spin state of the photo-sensitizer which induces such reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The overall effect is the increase in the population of the initial spin state of the RPs or RIPs. The micellar cage provides sufficient volume so that the component radicals of a pair are allowed to separate to such a distance where exchange interaction becomes negligible as well as spin correlation is still retained; therefore, spin flipping and subsequent geminate recombination are possible, which are the essential criteria for magnetic field effect (MFE) [12]. The fluorescence, laser flash photolysis and MFE studies indicate that ET occurs in organic homogeneous medium and it becomes predominant over H abstraction between AQ and micelle itself in micellar medium.…”
Section: Introductionmentioning
confidence: 99%